TINJAUAN YURIDIS TERHADAP PERUBAHAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 7 TAHUN 2017 TENTANG RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) TAHUN 2017-2022 - Sherly Permata Yendra; Mexsasai Indra; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In carrying out regional development, the government requires good and accurate development planning. Consistency and directed planning based on data which is an integral part of the regional planning process, it is accurate with the details of the terms and conditions of the Regional RPJM which are regulated in detail in the Domestic Regulation Number 86 of 2017. The methods and requirements of regional development planning must refer to the contained in the legislation on development planning in order to ensure consistency and the achievement of the objectives of development planning in the regions. In the Draft Regional Regulation Number 7 of 2017 concerning the Regional Medium-Term Development Plan (RPJMD) in Pekanbaru City which revised there were several problems which if viewed the implementation of the plenary meeting was not in accordance with the laws and regulations and government regulation 12 of 2018 concerning guidelines for the preparation of rules and regulations. Regional People's Representative Council so that no decision can be taken and the Draft Regional Regulation on the RPJMD which was proposed by the Mayor to the Governor of Riau Province in fact still exists.This research is a sociological juridical legal research, namely aresearch approach that emphasizes the legal aspects (laws and regulations) regarding the subject matter to be discussed, associated with the reality in the field. This study uses primary data sources consisting of primary, secondary, and tertiary legal materials.From the results of the research and discussion carried out, there are several conclusions obtained, namely: First, when viewed from the political aspect, the amendment to the regional regulation Number 7 of 2017 concerning the RPJMD has different views of the factions in the process of changing the regional regulation, which has generated a lot of prolonged controversy that is not yet clear. direction and urgency in making changes. And if viewed from a sociological aspect, changes to the RPJMD must be adjusted to the RPJPD and other national regional development direction documents, as well as the formation of the medium-term planning of the Pekanbaru City area that has not been fully implemented based on Permendagri Number 86 of 2017 in the formation of amendments to Regional Regulation Number 7 of 2017 concerning RPJMD. Keywords: RPJMD – Regional Development – Regional Regulatio